Transformation of Arabic Education Curriculum through Cyber Based Merdeka Belajar Kampus Merdeka and Outcome Based Education - Khasan Aedi; Nanin Sumiarni; Dita Aulia Nisa (ALSINATUNA, 2026)
The transformation of Universitas Islam Negeri (UIN) Syekh Nurjati Cirebon into Indonesia's first cyber university requires aligning the Arabic Education curriculum with The Outcome-Based Education (OBE) method and the Merdeka Belajar-Kampus Merdeka (MBKM) policy, including a minimum of 10% of cyber-content credits. This study develops a cyber-based MBKM curriculum within the OBE framework in the Arabic Education Department using a research and development (R&D) approach based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were gathered from 53 respondents through surveys, interviews, observation, document analysis, and focus group discussions, and were analyzed using a mixed-methods approach. The results show that the curriculum is well planned, that its design is adaptive and meets the cyber-content requirement, and that its implementation strengthens students’ pedagogical, professional, and digital competencies through activities such as teaching assistance, internships, and digital village projects. Questionnaire evaluation yielded a grand mean of 3.89–3.91 (Strongly Agree category), while expert validation reached 88.2% (Highly Feasible). Based on respondents’ perceptions and expert validation, the cyber-based MBKM curriculum is feasible and positively perceived, which points to its potential effectiveness, although it still requires stronger digital infrastructure, a better credit-conversion system, and closer coordination with external partners before it can be fully optimized. This study concludes that the developed curriculum design is feasible and well perceived, and is oriented toward producing competitive and transformative Arabic Education graduates in the digital era within a moderate Islamic education framework.